Empowering continuous maternal health and emergency care: the implementation of ARIMBI in Tirtorahayu Village - Kurniawan, Rahadian; Muhimmah, Izzati; Aziz, Muhammad Thariq; Fitriyati, Yasmini (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2025)
The 2023 data from Indonesia's Ministry of Health shows a high Maternal Mortality Rate (MMR) of 183 per 100,000 live births, far exceeding the target of 70. According to a WHO report in 2020, 75% of maternal deaths are caused by factors such as hemorrhage, infection, hypertension during pregnancy, prolonged labor, and abortion. Some of these factors could be anticipated if a responsive and integrated readiness system was in place to assist pregnant women. This article describes the implementation of the Sustainable Health Management Information and Emergency Application for Mothers (ARIMBI) in the village of Tirtorahayu, Subdistrict of Galur, Regency of Kulon Progo. From this implementation, there are two key areas to be addressed: easy access to blood donors and the availability of emergency transport for pregnant women. These measures are crucial for reducing MMR, and ensuring pregnant women get timely emergency assistance.